3D electroplated inductors with thickness variation for improved broadband performance. (25th October 2016) - Tseng, Victor Farm-Guoo; Bedair, Sarah S; Lazarus, Nathan
Abstract: The performance of an RF spiral inductor is based on the balance between ohmic losses in the outer turns and eddy current losses dominant in the inner turns where the magnetic field is the strongest. In this work, air-core spiral inductors with winding trace thicknesses decreasing towards the center are demonstrated, achieving quality factor improvement over a wide frequency range compared to uniform thickness inductors. A custom 3D copper electroplating process was used to produce spiral inductors with varying winding thicknesses in a single plating step, with patterned gaps in a seed layer used to create delays in the vertical plating. The fabricated center-lowered coil inductors were 80 nH within a one square millimeter area with thickness varying from 60 µ m to 10 µ m from outer to inner winding. Within the 16 MHz–160 MHz range, the center-lowered inductors were shown to have a maximum to minimum quality factor improvement of 90%–10% when compared to uniform thickness inductors with thicknesses ranging from 60 µ m to 10 µ m. Compared to the 20 µ m uniform thickness inductor which has the optimal performance among all uniform thickness inductors in this frequency range, the center-lowered inductors were shown to achieve a maximum quality factor improvement of 20% at the edge frequencies of 16 MHz and 160 MHz, and a minimum quality factor improvement of 10% near the geometric mean center frequency of 46 MHz.